Factors associated with Diabetes Mellitus among Tuberculosis Patients attending Tertiary Care Hospital in Delhi, India - Tiwari, Vijay Kumar; Verma, Piyush; Raj, Sherin (Indian Journal of Community Health, 2016)
Background: Worldwide increasing prevalence of DM may counteract the positive effects of improved curative services for TB. Aims & Objectives: To identify factors associated with Diabetes Mellitus among Tuberculosis Patients attending Tertiary Care Hospital in Delhi. Material & Methods: This study was conducted among 220 TB patients. Results: It was found that 16% were co-morbid. Among co-morbid patients, the age distribution skewed towards higher age groups as compared with only TB patients. Co-morbidity was higher among females (64%) as compared to males (36%). Higher percentage among Co-morbid patients (78%) belonged to lower socio-economic class compared to TB patients (58%). Statistically significant association of comorbidity was found with physical activity, dietary habits and tobacco/alcohol consumption. However, only one third of patients who were aware about DM, knew that diabetic patients are more prone to acquire TB infection. Among co-morbid cases, only 50% were aware that uncontrolled DM delays the cure of TB. Findings also suggested that the sputum conversion rate among the co-morbid patients was low compared with the only TB patients. Conclusion: The study concludes that counseling of patient with DM against higher risk of contracting TB and TB patients against delayed cure should be made as a part of national strategy to manage DM-TB comorbidity.